« Quoique plusieurs d’entre elles fussent probablement très jolies, elles n’en ont pas moins été expulsées » - Christophe Chevalier (Diasporas: Circulations, Migrations, Histoire)
The place and situation of women among foreign populations living in or passing through Belgium between 1830 and 1870 are still largely unknown. How were they received by the Belgian authorities? What factors influence the modalities of this reception and what reasons are given to justify their possible expulsion? What difficulties did they encounter on arrival in Belgium? Are there differences perceptible according to the socio-economic background and nationality of these women? By crossing the information from the files compiled by the Alien Police with the press of the time and various testimonies, this article aims to draw a more accurate portrait of female exile in Belgium through the prism of the policies adopted by the Sûreté publique against it.